(untitled) (Nordic Journal of African Studies, 2002)
The present paper is a descriptive study of a custom in Oromo culture (Ethiopia) known under the name of laguu or lagacha, which consists in avoiding mentioning the names of the persons who are relations by marriage. The topic deserves much attention as an ethnolinguistic phenomenon in the above-mentioned culture and on which nothing has been written so far. The study shows that because of language taboo, husband, wife and the in-laws avoid using their respective names and substitute for them several forms, most of which are coinings. The study analyses the taboo-words and describes the mechanisms used for finding substitutes.